1997
DOI: 10.1074/jbc.272.9.5457
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Properties and Sensitivity to Tentoxin of Chlamydomonas reinhardtii ATP Synthases Changed in Codon 83 of atpB by Site-directed Mutagenesis

Abstract: The participation of the amino acid ␤83 in determining the sensitivity of chloroplast ATP synthases to tentoxin was reported previously. We have changed codon 83 of the Chlamydomonas reinhardtii atpB gene by sitedirected mutagenesis to further examine the role of this amino acid in the response of the ATP synthase to tentoxin and in the mechanism of ATP synthesis and hydrolysis. Amino acid ␤83 was changed from Glu to Asp (␤E83D) and to Lys (␤E83K), and the highly conserved tetrapeptide ␤T82-E83-G84-L85 (⌬TEGL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…6, inset) did not enable the determination of the ratio of the bound CF 1 ␣ to the remaining RrF 1 ␣, the full inhibition of the hybrid containing both CF 1 ␣ and ␤ by tentoxin sets a lower limit of 1 mol CF 1 ␣ bound/mol of reconstituted RrF 0 F 1 /CF 1 . CF 1 ␤-Asp 83 was shown to be required for the inhibitory action of tentoxin and residues of different charge, such as lysine, or different spacer length such as glutamate, could not replace it (22,23). Table II illustrates that this aspartate is indeed essential for obtaining full inhibition by tentoxin in the presence of CF 1 ␣.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6, inset) did not enable the determination of the ratio of the bound CF 1 ␣ to the remaining RrF 1 ␣, the full inhibition of the hybrid containing both CF 1 ␣ and ␤ by tentoxin sets a lower limit of 1 mol CF 1 ␣ bound/mol of reconstituted RrF 0 F 1 /CF 1 . CF 1 ␤-Asp 83 was shown to be required for the inhibitory action of tentoxin and residues of different charge, such as lysine, or different spacer length such as glutamate, could not replace it (22,23). Table II illustrates that this aspartate is indeed essential for obtaining full inhibition by tentoxin in the presence of CF 1 ␣.…”
Section: Discussionmentioning
confidence: 97%
“…This result suggested that the ␤ subunit might be responsible for conferring tentoxin sensitivity to the F 1 enzyme. An aspartic acid residue at position 83 of CF 1 ␤ was indeed implicated as being essential for tentoxin sensitivity of the chloroplast CF 0 F 1 ATP synthase (22,23). However, the observation that the MgATPase activity of membranes isolated from an uncD-deleted Escherichia coli strain complemented with the chloroplast atpB gene was insensitive to tentoxin (24) suggests that additional CF 1 subunits might also be involved in conferral of this sensitivity.…”
mentioning
confidence: 81%
“…First, a high resolution structure of CF 1 is still lacking. Second, there is only indirect evidence (24,26) that ␤-Asp-83 2 takes part in the TTX binding site. However, for illustrating the TTX effects in relation to the CF 1 structure, we can take for granted that the TTX binding site is located in this region and that the structure of this well conserved domain is equivalent in CF 1 and MF 1 , although MF 1 is TTX-insensitive.…”
Section: Atp Interferes In a Complex Way With Ttx Binding At Its Secondmentioning
confidence: 99%
“…Both structures should promote additional contacts in the N-terminal crown-region of the F 1 complex, which might increase the thermal stability of the enzyme. In the thermophilic enzyme a hydrogen bond between ␤Asn 40 and ␣Arg 90 and van der Waal's interaction of residues ␤Asn 38 -␣Ser 21 and ␤Glu 41 -␣Met 48 are proposed to cause this increased stability (10). The high resolution structure of the chloroplast enzyme suggests that a salt bridge ␤Asp 83 -␣Arg 297 enhances the stability of the enzyme.…”
Section: The Structure Of the Chloroplast F 1 -Atpasementioning
confidence: 99%